(untitled) (Jagannath University Journal of Life and Earth Sciences, 2024)
Dhaka, the capital of Bangladesh, is located on the bank of the Buriganga River. Pollution of Buriganga river water with different types of waste containing antibiotic-resistant (AR) bacteria poses a threat to human health. Therefore, this study aims to analyze the physicochemical parameters, total aerobic bacterial count (TBC), total coliform count (TC), and antibiotic-resistant bacteria from waste disposal points located in the river seasonally. We collected 59 water samples from sewage waste (SW), 31 from industrial waste (IW), and 9 from hospital waste (HW) disposal sites during the wet (November to April) and dry (May to September) seasons in the Buriganga river. We found that water temperature, pH, BOD, and COD decreased, but water total dissolved solids (TDS) increased significantly in the dry season compared to the wet season. Bacteriological analysis showed that total TBC and TC were significantly increased in the dry season compared to the wet. Further analysis showed that TBC and TC from the water of SW and HW disposal sites increased in the dry season compared to the wet. However, TBC and TC from the water at IW disposal sites were not changed. These results indicate that SW and HW are the main contributors to the bacterial coliform contamination in the Buriganga River. Escherichia coli, Pseudomonas spp., Staphylococcus aureus, Streptococcus spp., and Salmonella spp. isolates showed a high prevalence of resistance against commonly used antibiotics. It can be concluded that SW and HW might spread AR bacteria in the water of the Buriganga River, which causes a significant threat to humans and the environment. Jagannath University Journal of Life and Earth Sciences, 9(2): 215-226, 2023 (December)